The Supply Chain Efficiency of Tilapia Farming in Floating Net Cage (FNC) in Wonogiri Regency - Dharmawan, Yan Eka; Siti Rahayu, Endang; Ferichani, Minar (Universitas Muhammadiyah Yogyakarta, 2020)
This study aims to determine the supply chain mechanism and analyze the supply chain efficiency of tilapia farming in floating net cage (FNC) in Wonogiri Regency. This research utilized the Data Envelopment Analysis (DEA) as the method. The research was conducted in Wonogiri and Wuryantoro Districts as the center of tilapia farming and other districts as marketing objectives. The research sample consisted of 50 tilapia farmers, 14 wholesalers, and 6 retailers. The data were collected using the snowball sampling method. The research used questionnaires and in-depth interviews. The results revealed that the structure of tilapia supply chain actors in Wonogiri Regency consisted of farmers, wholesalers, and retailers. As much as 35.71% of tilapia farmers chose to sell their products to wholesalers, 64.29% to retailers, and none sold directly to consumers. Based on performance measurement using the DEA method, the most efficient actors in the tilapia supply chain in Wonogiri Regency were wholesalers, with an average efficiency value of 0.998, followed by retailers with an average efficiency value of 0.982, and the most inefficient actors were farmers, with an average efficiency value of 0.789.